Peace operations : trends, progress, and prospects - Daniel, Donald C. (Donald Charles), 1944-; Taft, Patricia; Wiharta, Sharon (Georgetown University Press, 2008)
Trends in the number and scope of peace operations since 2000 evidence heightened international appreciation for their value in crisis-response and regional stabilization. Peace Operations: Trends, Progress, and Prospects addresses national and institutional capacities to undertake such operations, by going beyond what is available in previously published literature. Part one focuses on developments across regions and countries. It builds on data- gathering projects undertaken at Georgetown University's Center for Peace and Security Studies (CPASS), the Stockholm International Peace Research I.